THE INFLUENCE OF DIFFERENCES IN ETHNIC BACKGROUND AND COMMUNICATION PATTERNS ON THE PERFORMANCE OF HMTI ADMINISTRATORS (JETMI : JURNAL ILMIAH ERGONOMI, TEKNIK DAN MANAJEMEN INDUSTRI, 2025)
The phenomenon of inter-ethnic life in Indonesia is very interesting to study. Because, Indonesia which has various ethnic diversity, this country does not only belong to one ethnicity, so an attitude of tolerance is needed in communicating to remain conducive. This study aims to determine the effect of ethnic background on the performance of HMTI UKRI administrators. This research method uses a quantitative method with data collection techniques through questionnaires and statistical analysis. With a population of all HMTI members totaling 20 members and using multiple linear regression analysis in processing its data based on the results of research, discussion and test results described about ethnic background and communication patterns on HMTI performance, the communication pattern factor has a significant effect of 26.64% compared to the factor of differences in ethnic background which tends not to have a significant effect on the performance of HMTI administrators with a value of -3.4%.
Keywords: Ethnic_Background; Communication_Patterns; Organization; HMTI_Performance